Pengembangan Kinerja Tenaga Administrasi Sekolah Berbasis Teknologi Informasi - Resky Nuralisa Gunawan; S. Nudia Mastur; Udik Budi Wibowo (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2023)
This research aims to elucidate the challenges confronted by school administrative staff in the execution of their responsibilities and to identify avenues for enhancing their performance through the application of information technology. The chosen research methodology is a Systematic Literature Review (SLR) designed to recognize, evaluate, and interpret prior research findings. Out of 465 articles initially screened, 43 were meticulously reviewed for their relevance to the study's scope, with 18 articles ultimately included in this systematic literature review. The research findings underscore the pivotal role of information technology in providing student services by school administrative staff. Nevertheless, several issues surfaced post-implementation, including increased workloads, challenges related to coordination and communication, adaptations to policies and regulations, the utilization of technology and information systems, and issues concerning service quality and user satisfaction. Resolving these challenges necessitates identifying the staff's needs and competencies, offering suitable training and development opportunities, instituting a performance assessment system, enhancing accessibility and utilization of information technology, and sustaining ongoing monitoring and support.